Rocco Scotellaro or the impossibility of peasant literature - Carsaniga, Giovanni (Spunti e Ricerche, 2016)
In the post war Italians felt the need to revive the myth of popular culture. Readers readily accepted Carlo Levi’s notion of a "civiltà contadina". Some of the "originator" of "peasant" culture come in fact from other members of the society of which the peasants form part. In the case of Rocco Scotellaro one can see six functional categories of stylistic levels. These demonstrate that all he wrote can be traced to established literary tradition. Peasants can have a language-based art but it is not a writing-based art.